1987
DOI: 10.1152/jn.1987.58.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Inputs from regularly and irregularly discharging vestibular nerve afferents to secondary neurons in the vestibular nuclei of the squirrel monkey. II. Correlation with output pathways of secondary neurons

Abstract: 1. Intracellular recordings were made from secondary neurons in the vestibular nuclei of barbiturate-anesthetized squirrel monkeys. Monosynaptic excitatory postsynaptic potentials (EPSPs) evoked by stimulation of the ipsilateral vestibular nerve (Vi) were measured. An electrophysiological paradigm, described in the preceding paper (26), was used to determine the proportion of irregularly (I) and regularly (R) discharging Vi afferents making direct connections with individual secondary neurons. The results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
77
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(84 citation statements)
references
References 0 publications
6
77
1
Order By: Relevance
“…Goldberg et al (1987) showed that 75% of secondary vestibular neurons in the vestibular nucleus receive monosynaptic inputs from afferents with a broad range ofresponse properties. Highstein et al (1987) subdivided the population of secondary neurons according to their projection sites and found that 57% of identified interneurons in the VOR pathways received monosynaptic inputs from afferents with a broad range of response properties. However, Highstein et al (1987) interpreted the wide range of vestibular inputs to VOR interneurons as contamination of their sample with other "pause-burst" neurons and concluded that VOR pathways receive input mainly from afferents with regular spontaneous discharge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Goldberg et al (1987) showed that 75% of secondary vestibular neurons in the vestibular nucleus receive monosynaptic inputs from afferents with a broad range ofresponse properties. Highstein et al (1987) subdivided the population of secondary neurons according to their projection sites and found that 57% of identified interneurons in the VOR pathways received monosynaptic inputs from afferents with a broad range of response properties. However, Highstein et al (1987) interpreted the wide range of vestibular inputs to VOR interneurons as contamination of their sample with other "pause-burst" neurons and concluded that VOR pathways receive input mainly from afferents with regular spontaneous discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Highstein et al (1987) subdivided the population of secondary neurons according to their projection sites and found that 57% of identified interneurons in the VOR pathways received monosynaptic inputs from afferents with a broad range of response properties. However, Highstein et al (1987) interpreted the wide range of vestibular inputs to VOR interneurons as contamination of their sample with other "pause-burst" neurons and concluded that VOR pathways receive input mainly from afferents with regular spontaneous discharge. Our data disagree with the interpretation and Lisberger * Vestibular Inputs for the VOR of Highstein et al (1987) but agree with their data as well as in the gain of the VOR than are the eye movements evoked by with those of Goldberg et al (1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of these results, they concluded that irregular otolith afferents might be essential for the generation of steady-state nystagmus during off-vertical axis rotations (OVAR) and for velocity storage and the VOR at sinusoidal frequencies Ͻ0.1 Hz. The limited effects of irregular afferent "functional" ablation are surprising, as experimenters have also shown that there is no preferential innervation of second-order vestibular neurons by the different afferent types (Boyle et al 1992;Chen-Huang et al 1997;Highstein et al 1987). One possible explanation for this apparent paradox is the influence of extravestibular factors such as target distance or attention (Chen-Huang et al 1997;Chen-Huang and McCrea 1998) on the responses of neurons within the vestibular nucleus.…”
mentioning
confidence: 99%